Rancang Bangun Aplikasi Tracking Untuk Status Order Berbasis Web Pada PT SUCOFINDO Cabang Surabaya - Herman, Herman; Wibowo, Januar; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT Sucofindo ( Superintending Company Of Indonesia ) working in the area of inspection ( commercial ) , audit ( project ) , testing ( project ) , analysis ( laboratory ) , certification services ( project ) , and training service ( project ) .Activities new orders were done of administration has decreased in competence services inspection .One of the causes was the absence of information that supports the process of the order in disallow module loading .The information of them information status order and selection task .To overcome the problems built an application web-based that can be used to re tracking status order .This application can be accessed by head of the assignor work ( head of ptk ) and other interested parties via web so that it can be display information status order and provided information about invoice and certificates on time , meanwhile, the process task in employees can was in full. Based on the results of the trial that has done together with pt sucofindo the branch of surabaya , the application was able to display information the status of the order started order accepted until order finished .In addition the application evaluation can provide status so that the service order inspection services can run a maximumKata Kunci : Order, Application, Tracking, PT Sucofindo.